1999
DOI: 10.1144/gsl.sp.1999.156.01.16
|View full text |Cite
|
Sign up to set email alerts
|

Late Neogene sedimentary facies and sequences in the Pannonian Basin, Hungary

Abstract: Detailed sedimentological, facies and numerical cycle analysis, combined with magnetostratigraphy, have been made in a number of boreholes in the Pannonian Basin, in order to study the causes of relative water-level changes and the history of the basin subsidence. Subsidence and infilling of the Pannonian Basin, which was an isolated lake at that time occurred mainly during the Late Miocene and Pliocene. The subsidence history was remarkably different in the individual sub-basins: early thermal subsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…No clear evidence of a regional erosional unconformity was found in the post‐kinematic deposits in the southern part of the basin; that is a marked difference from the central and northern part of the basin, where a significant local unconformity is present (e.g. Csato, ; Juhász et al ., ) that is debated to have resulted either from the MSC or from tectonic inversion. Both processes can cause a drop of relative sea/lake level, but in different ways; the MSC would have caused an absolute drop that affected the entire basin.…”
Section: Discussion: Controls On the Late Miocene Progradational Infimentioning
confidence: 85%
See 1 more Smart Citation
“…No clear evidence of a regional erosional unconformity was found in the post‐kinematic deposits in the southern part of the basin; that is a marked difference from the central and northern part of the basin, where a significant local unconformity is present (e.g. Csato, ; Juhász et al ., ) that is debated to have resulted either from the MSC or from tectonic inversion. Both processes can cause a drop of relative sea/lake level, but in different ways; the MSC would have caused an absolute drop that affected the entire basin.…”
Section: Discussion: Controls On the Late Miocene Progradational Infimentioning
confidence: 85%
“…The debate on the effects of the MSC on the Pannonian Basin focuses on the genesis of this unconformity: one group of studies suggests that the unconformity is related to differential tectonic uplift that took place during the onset of the latest Miocene–Quaternary inversion, which was superposed over a longer term alternation of aggradational and progradational deposition (Horváth et al ., ; Magyar & Sztanó, ; Sztanó et al ., ). Other studies argue for a significant base level drop in the Central Paratethys as a result of the Messinian Salinity Crisis (MSC) (Csató, ; Juhász et al ., ; Csato et al ., , ; Suc et al ., and references therein). This event should have been coeval with the 50–200 m MSC sea‐level drop in the eastern neighbouring Dacian Basin (Leever et al ., , ) and with a much larger drop in the Black Sea (Munteanu et al ., ).…”
Section: Formation and Development Of The Pannonian Basin And Lake Pamentioning
confidence: 99%
“…This issue was central to subsequent investigations involving quantitative subsidence analyses (backstripping) of an extended set of Pannonian Basin wells and cross sections and their forward modeling (Juhász et al, 1999;Lankreijer et al, 1995;Lenkey, 1999;Sachsenhofer et al, 1997). Kinematic modeling, incorporating the concept of necking depth and finite strength of the lithosphere during and after rifting (Van Balen et al, 1999), as well as dynamic modeling studies (Huismans et al, 2001b), suggested that the transition from passive to active rifting was controlled by the onset of subcrustal flow and small-scale convection in the asthenosphere.…”
Section: Stretching Models and Subsidence Analysismentioning
confidence: 99%
“…5.0 Ma) is likely to be associated with a stratigraphic gap (Juhász et al, 1999) and significant tectonic overprint as suggested by the general tectono-stratigraphic patterns within the Neogene basin fill. The higher rank unit bounded by Pan-1 SB and Pan-4 SB approximately correlates with the Tortonian-Messinian strata of the standard time scale.…”
Section: Sequence Stratigraphymentioning
confidence: 92%
“…Iharosberény-I well log has been correlated with the global magnetic polarity scale (Kande andKent, 1995, Berggren et al, 1995) and seismic reflectors in the Southern Transdanubia. The obtained sequence stratigraphic framework was tied to a regional biostratigraphic and magnetostratigraphic framework recently developed for the Upper Miocene succession of the Pannonian basin (Juhász et al, 1999;Magyar et al, 1999a, b;Müller et al, 1999). Radiometric data on volcanic rocks interbedded within the Upper Miocene continental strata of western Hungary were also used to constrain chronostratigraphic interpretation (Balogh et al, 1986;Balogh, 1995;Pécskay et al, 1995).…”
Section: The Regional Stratigraphic Framework Of Sw Pannonian Basinmentioning
confidence: 99%